The Hirtodrosophila melanderi species group (Diptera: Drosophilidae) from the Huanglong National Nature Reserve, Sichuan, China - Mei, Yu; Katoh, Takehiro K.; Gao, Jian-Jun (Zootaxa, 2019)
The Hirtodrosophila melanderi species group is currently known for thirteen described species, most of which were thought to be fungivorous. More than half known species of this species group were recorded exclusively from high altitude zone to the southeast of the Qinghai-Tibet Plateau in China. In our recent field survey in the Huanglong National Nature Reserve (located to the east of the Qinghai-Tibet Plateau) in Sichuan Province, China, we collected dozens of specimens of the H. melanderi group there. In the present study, these specimens are subjected to species delimitation based on data of not only morphology, but also DNA barcodes (nucleotide sequences of a 658-bp fragment of the mitochondrial cytochrome c oxidase subunit I gene). The five new species thus recognized are described: Hirtodrosophila minshanensis sp. nov., H. lambda sp. nov., H. zhangae sp. nov., H. zouae sp. nov., and H. nigrispina sp. nov. In addition, an updated key to all species of the H. melanderi species group is provided.